KOLABORASI KONSERVASI DI KAWASAN WISATA CIWIDEY - Ely Triana; Hadi S Alikodra; Tutut Sunarminto; Adjat Sudrajat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Collaboration of conservation must be a way in sustainable tourism development. The research aimed to evaluate the factual condition of collaboration of conservation and to formulate the strategies to improve the capacities of collaboration of conservation in Ciwidey tourism area. Analysis of conservation, sustainable tourism and collaboration objective aspects were conducted by distributing quetionnaire and interview the stakeholder. The data were analyzed by score mapping, gap and modified SWOT analysis. The result show that factual condition of collaboration of conservation in three location which are Kawah Putih, TWA Cimanggu and Situ Patenggang were valued fair to passable. The strategies to improve capacities of collaboration of conservation in Ciwidey tourism area are divided in three levels: 1) system level: to make policy which regulate the formation of an institution, for example a forum of conservation and ecotourism which include all stakeholders; and to build an integrated tourism transportation system and public facilities; 2) organization level: to include conservation and sustainable tourism aspects in the organization planning and programs in accordance to their authority and main tasks; 3) individual level: to improve the knowledge and skill of conservation and sustainable tourism for everyone who get involved in tourism activity by way of counseling and training. Keyword: Ciwidey tourism area, Collaboration, Conservation, Strategy, Sustainable tourism.